Ceramic form and function in the Neolithic Gulf. A view from Bahra 1. (10th October 2019) - Smogorzewska, Anna
Abstract: This paper discusses the possible functions of ceramic vessels in the Neolithic Gulf, based on new data from the Ubaid‐related settlement of Bahra 1 (Kuwait). Two pottery groups identified at the site—Ubaid Ware and Coarse Red Ware—are found in great numbers and variety of forms which provides grounds for a reconsideration of the role of pottery vessels in the societies of the Gulf. Analysis of this material reveals a more varied function of pottery vessels compared to that suggested in earlier studies. It was also possible to define the function of certain pottery vessels in more detail, both in their economic and social context.